Recombination facilitates genetic assimilation of new traits in gene regulatory networks. Issue 5 (29th August 2021) - Espinosa‐Soto, Carlos; Hernández, Ulises; Posadas‐García, Yuridia S.
Abstract: A new phenotypic variant may appear first in organisms through plasticity, that is, as a response to an environmental signal or other nongenetic perturbation. If such trait is beneficial, selection may increase the frequency of alleles that enable and facilitate its development. Thus, genes may take control of such traits, decreasing dependence on nongenetic disturbances, in a process called genetic assimilation. Despite an increasing amount of empirical studies supporting genetic assimilation, its significance is still controversial. Whether genetic assimilation is widespread depends, to a great extent, on how easily mutation and recombination reduce the trait's dependence on nongenetic perturbations. Previous research suggests that this is the case for mutations. Here we use simulations of gene regulatory network dynamics to address this issue with respect to recombination. We find that recombinant offspring of parents that produce a new phenotype through plasticity are more likely to produce the same phenotype without requiring any perturbation. They are also prone to preserve the ability to produce that phenotype after genetic and nongenetic perturbations. Our work also suggests that ancestral plasticity can play an important role for setting the course that evolution takes. In sum, our results indicate that the manner in which phenotypic variation maps unto genetic variation facilitates evolution through genetic assimilation in gene regulatory networks. Thus, we contend that the importance of this evolutionary mechanism should not be easily neglected. Abstract : Recombination facilitates genetic assimilation of new gene activity patterns. Recombinant offspring of parents with the ability to produce a certain gene activity pattern B after nongenetic perturbations are more prone to yield offspring that produce B in the absence of perturbations (small black circles) and that preserve the ability to produce B through plasticity (small bicolored circles) or through mutation (not shown). Therefore, if selection increases the frequency of organisms that produce B through plasticity (bicolored circles) at the expense of those unable to produce B (white circles), the appearance of organisms that do not require any perturbation to produce B (black circles) will be easier through either recombination or mutation.